Linguistic games and the communicative ability of five-year-old boys and girls from an initial public educational institution - Mejía Bustillos, Blanca (2018)
The main objective of the study was to demonstrate the influence of language games on the development of communication skills of children of five years of initial education. The approach adopted corresponded to the qualitative one; the type of research, descriptive correlational; and the design, not experimental. We worked with a sample of 60 children (as). The selection criteria was intentional because it was a small population. During the research process, emphasis was placed on the management of a set of recreational resources related to language management in order to develop the capacities with respect to the oral and written use of the same, starting from the distinction of the initial and final sounds of the words, added to the fun and entertaining exercise of the mouth muscle to facilitate speech fluency. From their results it is summarized that the systematic and organized application of linguistic games has a significant and strong relationship with the development of children's oral and written communication skills, as well as with psycho-social development, with training of personality and with the practice of basic social values.